The Development of Sustainable Cultural Heritage Tourism in Malaysia: Implication for Planning and Management - Hamimi, Omar (2013)
This thesis examines the development of cultural heritage tourism in Malaysia, and questions if this tourism development has been managed in a sustainable manner. Recent national tourism policies in Malaysia increasingly have been aimed towards promoting cultural heritage tourism, signifying that cultural heritage tourism could be potentially one of the most important areas in the growth of the country’s tourism industry. While tourism development has contributed to the country’s economic growth, for cultural heritage, the thrust of the tourism industry is to make the most of the country’s non-renewable resources. This thesis identifies three key objectives required for creating sustainable tourism development in Malaysia: meeting the needs of local communities, satisfying the demands of a growing number of tourists, and safeguarding the remaining natural and cultural resources. Knowledge leading to improvements in the development of cultural heritage tourism is important, as knowledge is a primary means of strengthening its positive aspects and simultaneously mitigating its negative aspects, so that development can maintain a long-term viability. This study also explores some of the key management issues relating to the development of cultural heritage tourism at both Federal and State levels. A broad understanding is necessary for providing a firm basis in prescribing a thorough and realistic sustainable development framework. The study employs questionnaires, surveys, and interviews with a range of government officials, local communities, and tourists. The findings indicate that the government has played a major role in shaping the development of sustainable cultural heritage tourism in Malaysia, but at present there are many shortcomings that need to be addressed, such as definitions of the term Cultural Heritage, as well as management issues, including conflicts and bureaucratic barriers. These problems, consequently, hinder a comprehensive management of cultural heritage tourism. Additional findings indicate that local communities are not actively involved in tourism planning or decision-making processes, though they generally are satisfied with development at the locations of this study. The study also calls for higher quality tourist services, and the promotion of other elements of cultural heritage to compliment the already established yet limited elements. Finally, it suggests a Sustainable Cultural Heritage Tourism Framework, incorporating social and cultural elements. This thesis contributes new knowledge to the field of cultural heritage tourism in Malaysia and may serve as a starting point for researchers interested in this area. Furthermore, the results of this study are expected to be useful for guiding policy actions in the future.